Leadership, Motivation, and Work Ethic Effects on Employee Performance in the Automotive Industry - Joonner Rambe; Mohamad Razab Iryadana; Mohammad Sidik Priadana (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The automotive industry is facing increasingly intense competition, requiring companies to improve employee performance to remain competitive. This study aims to analyze the influence of transformational leadership, competence, motivation, and entrepreneurial spirit on work ethic and employee performance in large automotive companies in the region. The method used in this study is a quantitative approach with path analysis to examine the direct and indirect relationships between variables. All statistical analyses were performed using SPSS version 27 to ensure accuracy and consistency. The results show that motivation has the greatest impact on work ethic, followed by transformational leadership, competence, and entrepreneurial spirit. In addition, work ethic has a significant positive influence on employee performance. These findings indicate that strengthening motivation, inspirational leadership, enhancing competence, and fostering entrepreneurial spirit can improve work ethic, which in turn contributes to improving employee performance. In conclusion, companies need to strengthen leadership programs, training, and human resource development to enhance work ethic and performance in the competitive automotive industry.